Near Optimal PID Controller Tuning: Interval Arithmetic Approach. (2020) - Patel, Pritesh; Janardhanan, S
Abstract: In this paper, a near-optimal tuning method for PID controller which is based on minimizing the Integral Square Error (ISE) is presented. Parseval's theorem is used to find the ISE as a function of controller parameters. Guaranteed optimization of the ISE is achieved using the Moore Skelboe Algorithm and interval analysis for the given range of the controller parameter. For stability assurance, Routh Hurwitz criterion is used. This method is effective for finding PID values for given initial range and applicable for all first and second order linear time-invariant (LTI) system and some of the higher-order LTI systems. Simulation results are presented using the MATLAB and INTLAB software. Experimental results are presented for pitch and yaw angle control of Twin Rotor Multiple Input Multiple Output (MIMO) system.